Color translucent head-up display based on a segmented Fourier hologram - Suszek, Jaroslaw; Sypek, Maciej; Siemion, Andrzej; Fajst, Agnieszka; Makowski, Michal; Kolodziejczyk, Andrzej (Photonics Letters of Poland, 2009)
The paper presents the numerical and experimental results of reconstructing images from a spatially segmented Fourier hologram with additional carrier frequencies, acting as a translucent head-up display (HUD). Successful reconstructions of colorful images visible at the infinity were achieved. The design procedure is described and some limitations of the method are discussed, like the appearance of ghost images. Exemplary results from numerical and real experiments are given. In order to obtain color images three beams of primary colors were successfully utilized to create a color mixture. Full text: PDF References: A. Ramsbottom, S. Sergeant, D. Sheel, "Holography for automotive head-up displays", Proc. SPIE 1667, 146-164 (1992).[CrossRef] T. Matsumoto, S. Eguchi, F. Yamagishi, M. Nakashima, "Compact holographic head-up display", Proc. SPIE 2652, 341-344 (1996).[CrossRef] J. Suszek, M. Makowski, M. Sypek, A. Siemion, A. Kolodziejczyk, "Angle-dependent encoding of multiple asymmetric symbols in a binary phase hologram with a spatial segmentation", Appl. Opt. 48, 270-275 (2009).[CrossRef] R. W. Gerchberg, W. O. Saxton, Optik 35, 237-246 (1972).